Body Mass Index and Clinical Response to Tocilizumab in Patients With Rheumatoid Arthritis - Hua HUANG,; Han CEN,; Li ZHOU,; Ting-hui WANG,; Wen QIN,; Bin-hua XIE,; Dong-Mei XIAO,; Xiu-Di WU,; Hua-Xiang WU, (Archives of Rheumatology, 2019)
Objectives: This study aims to determine whether baseline body mass index (BMI) affects clinical response to tocilizumab (TCZ) after six months of treatment in rheumatoid arthritis (RA) patients. Patients and methods: In this prospective study, a total of 52 RA patients (10 males, 42 females; mean age 50.6±12.2 years; range, 23 to 73 years) receiving intravenous TCZ were consecutively recruited and followed-up for six months. BMI was calculated before initiation of TCZ treatment. The primary clinical response criterion was clinical disease activity index (CDAI) low disease activity (LDA) and the secondary clinical response criteria included CDAI remission, disease activity score based on 28 joints (DAS28)-erythrocyte sedimentation rate (ESR) LDA, DAS28-ESR remission, European League Against Rheumatism (EULAR) good response, and decreased DAS28-ESR (ΔDAS28-ESR)≥1.2. Results: The number of RA patients classified as normal weight, overweight, and obese according to baseline BMI was 38 (73.1%), eight (15.4%), and six (11.5%), respectively. Similar baseline BMI median levels were found between RA patients reaching CDAI LDA and non-LDA: 21.11 (18.94-23.72) versus 20.78 (20.03-22.29) (p=0.98), and non-significant difference in the proportion of responders between normal weight and overweight/obese RA patients was found (p=0.47). No significant difference was found when the secondary clinical response criteria were applied. Conclusion: Our study demonstrates that BMI is not associated with clinical response to TCZ among RA patients and TCZ may be used to treat RA patients regardless of BMI levels.